The never-ending battle between proximal row carpectomy and four corner arthrodesis: A systematic review and meta-analysis for the final verdict. Issue 2 (February 2022) - Ahmadi, Ali R.; Duraku, Liron S.; van der Oest, Mark J.W.; Hundepool, Caroline A.; Selles, Ruud W.; Zuidam, J. Michiel
Summary: While scaphoid excision combined with Four Corner Arthrodesis (FCA) or Proximal Row Carpectomy (PRC) is a commonly-used salvage procedures to treat type two and type three Scapholunate Advanced Collapse (SLAC) and Scaphoid Nonunion Advanced Collapse (SNAC)-induced degenerative arthritis, controversy remains over which treatment intervention provides superior outcomes. We searched for articles comparing a range of motion, grip strength, complications requiring reoperation, conversion to wrist arthrodesis, pain, and disability of shoulder and arm scores between FCA and PRC-treated patients. The risk of bias was assessed using the National Institutes of Health (NIH) quality assessment tool. We performed a meta-analysis using Random-Effects Models. Fifteen articles (10 retrospective, 2 cross-sectional, 1 prospective, and 2 randomized trials) were included. There was no significant difference between PRC and FCA in any of the different outcome measures. The risk of bias was found consistently high across all studies. Despite the lack of high-quality evidence, based on existing literature, we recommend PRC as the preferred choice of treatment because of the simplicity of the surgical procedure, lack of hardware-related complications, and comparable long-term outcomes. Level of evidence: III - Therapeutic